E-023 Interventional approaches to tandem internal carotid artery/middle cerebral artery occlusions treated with carotid angioplasty vs stenting: a case series and discussion. (4th July 2012) - Telischak, N; Zarzour, H; Dinobile, D; Frerichs, K; Thomas, A; Selim, M; Reddy, A
Abstract : We report on the techniques of simultaneous carotid artery angioplasty and/or stenting with intracranial thrombectomy and/or thrombolysis in the treatment of acute stroke due to tandem ICA/MCA occlusion. A review of the interventional neuroradiology patient database of two major teaching hospitals (Beth Israel Deaconess Medical Center and Brigham and Women's Hospital, Boston, Massachusetts, USA) yielded five cases from the past 2 years of treatment of tandem ICA/MCA occlusion. Five patients presented to our hospitals between 12/2008 and 12/2010 (mean age: 65.8, range 48–84 years) with acute stroke (mean NIHSS: 18, range 8–24) and were found to have tandem ICA/MCA occlusion (Abstract E-023 table 1 ). Definitive interventional neuroradiology treatment (mean time from symptom onset to catheterization: 168 min, range 100–251 min) either treated with carotid artery angioplasty (N=2), or angioplasty and stent placement (N=3) combined with intracranial intra-arterial thrombolysis and/or mechanical clot retrieval. Procedures were technically successful in opening the ICA occlusion in all cases, with variable results in intracranial thrombectomy/thrombolysis ranging from complete revascularization to residual M1 branch MCA occlusion. All patients survived to hospital discharge with residual neurologic deficits. We review treatment options of carotid angioplasty alone vs angioplasty and stent placement, in addition to intracranial thrombolysis and mechanical thrombectomy, and discuss potential pitfalls to these approaches. Competing interests: None.